The ecclesiastical history of Evagrius Scholasticus - Euagrios Scholastikos, 536-593 (Translated texts for historians, 2000)
The Ecclesiastical History of Evagrius narrates the history of the church from the start of the Nestorian controversy in 428 until the death of Evagrius’ employer, Patriarch Gregory of Antioch Gregory in 592. It is our best continuous account of these ecclesiastical events and provides an important narrative of disputes within the church in the fifth century, which includes substantial quotations from relevant contemporary documents, some of them unique. This book will be an indispensable tool for anyone interested in late antiquity and is to be highly commended for its thorough and lucid scholarship.